Life goals in patients with cancer: a systematic review of the literature. Issue 4 (19th May 2015) - Hullmann, Stephanie E.; Robb, Sheri L.; Rand, Kevin L.
Abstract: Objective: Purposes of this systematic review of life goal research in cancer patients were to (1) identify life goal characteristics and processes being examined, (2) describe instruments used to assess life goal constructs, (3) identify theoretical models being used to guide research, and (4) summarize what is known about the impact of the cancer experience on life goal characteristics, processes, and psychological outcomes. Methods: We conducted this systematic review using MEDLINE, PubMed, CINAHL, and PsycINFO databases. Inclusion criteria were as follows: (1) published between 1993 and 2014, (2) English language, (3) cancer patient population, and (4) original research articles that assessed life goal characteristics and/or goal processes. One hundred ninety‐seven articles were screened and 27 included in the final review. Results: Seven life goal characteristics and seven life goal processes were identified, and less than half of studies investigated associations between goal characteristics and processes. Conceptual definitions were not provided for about half of the identified life goal constructs. Studies used both validated and author‐developed instruments to assess goal constructs. Twenty‐four different theoretical models were identified, with self‐regulation theory most frequently cited. Overall, the literature suggests that cancer impacts patients' life goal characteristics and processes, and life goal disturbance is related to poorer psychological outcomes. Conclusions: The impact of the cancer experience on life goals is an important and emerging area of research that would benefit from conceptual and theoretical clarity and measurement consistency. Copyright © 2015 John Wiley & Sons, Ltd.